TALK ABOUT “HOOKING UP”: HOW COLLEGE STUDENTS‟ ACCOUNTS OF “HOOKING UP” IN SOCIAL NETWORKS INFLUENCES ENGAGING IN RISKY SEXUAL BEHAVIOR - Olson, Amanda J (2009)
The study focused on how narratives told among social network participants can create a “culture of encouragement” surrounding risky sexual short-term relationships. The study adopted a social network approach to examine the “hookup” culture and risky sexual behavior. Specifically, this study examines who students are talking to, how frequently they discuss sexual experiences, and the specific accounts they discuss in connection with the hookup culture. Two research questions were asked to understand participants‟ personal definitions of hooking up and what factors lead to engaging in a hookup. The researcher also hypothesized that network closeness, frequency, and range would influence an individual‟s attitude and behavior about non-relationship sex. The study found that the more individuals discuss hooking up with their social network, the more they report approving of and participating in non-relationship sex. Also, the most common hookup scripts described in this study were those that are social (network present). The results of this study revealed that hooking up does occur on college campuses and individuals‟ networks do influence their self-approval and participation in non-relationship sex